Nanomaterials-based sensitive electrochemiluminescence biosensing. (February 2017) - Chen, Ying; Zhou, Shiwei; Li, Lingling; Zhu, Jun-jie
Graphical abstract: Highlights: The great potential of multifunctional nanomaterials for ECL bioanalysis is presented. Deep insights into nanomaterials-based ECL biosensing strategies are discussed. Recent significant developments of nanomaterials-based ECL biosensors are reviewed. Novel applications of ECL resonance energy transfer and ECL imaging are highlighted. Future challenges and prospects of nanomaterials-based ECL bioanalysis are concluded. Abstract: Nanomaterials with wonderful optical, electrical and chemical properties are widely studied in recent decades. In electrochemiluminescence (ECL) sensing area, nanomaterials have also gained crescent attention for their excellent performance based on different functions, such as innovative luminophores, molecule carriers, electrode modification materials and reaction catalysts. Deep insight into ECL biosensing strategies with multifunctional nanomaterials will benefit the design of advanced sensors. Based on this, nanomaterials-based ECL biosensors have shown more promising potentials than traditional ones in analytical applications. After a brief overview of basic ECL principles and sensing approaches, herein, a general description of nanomaterials-based ECL biosensing is presented, especially with emphasis on recently developed ECL resonance energy transfer (ECL-RET) strategy. Finally, future outlooks are considered in building sensitive ECL biosensors.